2015
DOI: 10.4314/sajas.v45i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rhus coriaria on nutrient composition, thiobarbituric acid reactive substances and colour of thigh meat in heat-stressed broilers

Abstract: Heat stress negatively affects the meat quality in broiler chickens, as indicated by lipid peroxidation. The aim of this study was to investigate the effects of 0.0, 2.5, 5.0 and 10 g sumac fruit powder/kg of the diet, along with 100 mg α-tocopherol acetate (AT)/kg as antioxidants, on meat characteristics of broilers under heat stress conditions. Consumption of 5.0 g sumac/kg decreased the thiobarbituric acid reactive substance (TBARS) concentration in thigh meat. The thigh meat pH increased only as a result o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…Sumac's antioxidant properties are reported because of Phenolic compounds. This is probably due to the reduction of quail egg cholesterol by sumac due to the compounds present in this plant (Sharbati et al, 2015). Similar results were found by Habibi and Ghahtan (2019) who reported that the dietary addition of 20 g/kg R. coriaria powder reduced cholesterol levels on quail.…”
Section: Egg Biochemical Factorssupporting
confidence: 84%
See 2 more Smart Citations
“…Sumac's antioxidant properties are reported because of Phenolic compounds. This is probably due to the reduction of quail egg cholesterol by sumac due to the compounds present in this plant (Sharbati et al, 2015). Similar results were found by Habibi and Ghahtan (2019) who reported that the dietary addition of 20 g/kg R. coriaria powder reduced cholesterol levels on quail.…”
Section: Egg Biochemical Factorssupporting
confidence: 84%
“…Higher levels will have a negative effect on egg production and quality in layers as shown by increased cholesterol level (Saki et al, 2014a). P. granatum and R. coriaria are medicinal plants with antioxidant properties (Sharbati et al, 2015;Yassein et al, 2015). It seems that an increase in yolk quality by S. cristafolium is due to antioxidative properties of S. cristafolium.…”
Section: Treatment Egg Weight (G) Weekly Egg Production (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this problem, different levels of Sumac were used as a feed supplement for the chicken and compared to Alpha tocopherol acetate as a control. At the end of the experiment, the pH of thigh meat was measured with a digital pH meter and TBARS was determined using trichloroacetic acid (TCA) and measuring absorbance using a spectrophotometer (Sharbati et al, 2015). The birds treated with a medium level of sumac showed the lowest thigh TBARS compared to the non-treated birds.…”
Section: Sumac Use In Feed Additivementioning
confidence: 99%
“…Studies on feed and food supplementation of polyphenols showed increased antioxidant capacity in blood and in several organs [ 16 ]. Antioxidative effects of the dietary supplementation with phenolic compounds from various sources had been extensively studied in sheep [ 19 ], broilers [ 20 22 ], rabbits [ 23 ], and turkeys [ 24 ]. More recently, Akbarian et al [ 25 ] examined the effects of dietary essential oils (rich in simple phenolic compounds) on mRNA levels of heat shock protein 70 (HSP70) and antioxidant enzymes, oxidative status, and meat oxidative stability of heat stressed broilers.…”
Section: Discussionmentioning
confidence: 99%